Concordance in phylogeography and ecological niche modelling identify dispersal corridors for reptiles in arid Australia. (10th June 2016) - Melville, Jane; Haines, Margaret L.; Hale, Joshua; Chapple, Stephanie; Ritchie, Euan G.
Abstract: Aim: Using the rock‐specialist agamid Ctenophorus caudicinctus as a model, we test hypothesized biogeographical dispersal corridors for lizards in the Australian arid zone (across the western sand deserts), and assess how these dispersal routes have shaped phylogeographical structuring. Location: Arid and semi‐arid Australia. Methods: We sequenced a c . 1400 bp fragment of mtDNA ( ND2 ) for 134 individuals of C. caudicinctus as well as a subset of each of the mtDNA clades for five nuclear loci ( BDNF, BACH1, GAPD, NTF3, and PRLR ). We used phylogenetic methods to assess biogeographical patterns within C. caudicinctus, including relaxed molecular clock analyses to estimate divergence times. Ecological niche modelling (Maxent ) was employed to estimate the current distribution of suitable climatic envelopes for each lineage. Results: Phylogenetic analyses identified two deeply divergent mtDNA clades within C. caudicinctus – an eastern and western clade – separated by the Western Australian sand deserts. However, divergences pre‐date the Pleistocene sand deserts. Phylogenetic analyses of the nuclear DNA data sets generally support major mtDNA clades, suggesting past connections between the western C. c. caudicinctus populations in far eastern Pilbara (EP) and the lineages to the east of the sand deserts. Ecological niche modelling supports the continued suitability of climatic conditions between the Central Ranges and the far EP for C. c. graafi . Main conclusions: Estimates of lineage ages provide evidence of divergence between eastern and western clades during the Miocene with subsequent secondary contact during the Pliocene. Our results suggest that this secondary contact occurred via dispersal between the Central Ranges and the far EP, rather than the more southerly Giles Corridor. These events precede the origins of the western sand deserts and divergence patterns instead appear associated with Miocene and Pliocene climate change.